1996
DOI: 10.1091/mbc.7.6.907
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 32 mutations from X-linked Charcot-Marie-Tooth disease patients: functional defects and dominant negative effects.

Abstract: We have characterized the function of connexin (Cx) 32 gene mutations found in X-linked dominant Charcot-Marie-Tooth disease with respect to their ability to form functional gap junctions among themselves and to inactivate wild-type Cx32 by a dominant negative mechanism. We prepared four types of Cx32 mutant cDNAs and transfected them into HeLa cells, which do not show detectable levels of gap junctional intercellular communication (GJIC), nor expression of any connexins examined. Cells transfected with the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 37 publications
7
120
0
2
Order By: Relevance
“…A dominant negative effect, loss of function effect, and interaction among different connexins have been proposed to explain the molecular mechanism of the genotype/ phenotype correlation in CMTX (Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Hahn et al 1999;Nicholson et al 1999;Fischbeck et al 1999). However, it is uncertain whether the patients with mutant Cx32 who were investigated in the expression study of mutant Cx32 in culture cells showed unusual symptoms of CMTX, such as CNS involvement (Bruzzone et al 1994;Omori et al 1996;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Nicholson et al 1999;Fischbeck et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dominant negative effect, loss of function effect, and interaction among different connexins have been proposed to explain the molecular mechanism of the genotype/ phenotype correlation in CMTX (Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Hahn et al 1999;Nicholson et al 1999;Fischbeck et al 1999). However, it is uncertain whether the patients with mutant Cx32 who were investigated in the expression study of mutant Cx32 in culture cells showed unusual symptoms of CMTX, such as CNS involvement (Bruzzone et al 1994;Omori et al 1996;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Nicholson et al 1999;Fischbeck et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1993, more than 200 different mutations, affecting every portion of the gene (Bergoffen et al 1993, Fairweather et al 1994Ionasescu 1995;Ionasescu et al 1994Ionasescu et al , 1996Bone et al 1995Bone et al , 1997Fischbeck et al 1996;Janssen et al 1997;Birouk et al 1998;Sander et al 1998;Nelis et al 1999;Hahn et al 1999), have been identified. However, only several mutations have been investigated in terms of their ability to form functional gap junctions and in terms of their relations with other connexins (Bruzzone et al 1994;Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Nicholson and Corbett 1999;Fischbeck et al 1999).…”
Section: X-linkedmentioning
confidence: 99%
“…Compensatory effects by other oligodendrocytic connexins expressed may account for the lack of such CNS phenotypes in most CMT1X patients. Expression studies of several CMT1X mutations have shown that many of the mutated proteins, including all the ones known to cause CNS phenotypes, are retained intracellularly in the Golgi apparatus or endoplasmic reticulum (ER), with reduced or absent GJ formation (Deschênes et al 1997;Kleopa et al 2002;Oh et al 1997;Omori et al 1996;VanSlyke et al 2000;Yum et al 2002). Patients who have a GJB1/Cx32 deletion do not appear to have a CNS phenotype (Hahn et al 2000), indicating that loss of Cx32 function alone is not detrimental to oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Cx32 mutations that cause clinical CNS manifestations are therefore likely to cause abnormal gain of function, for example through trans-dominant negative effects on other human oligodendrocytic connexins. There are precedents for connexin mutants having such gain of function: Cx32 mutations that cause CMT1X caused impairment of GJ function of the coexpressed wild type Cx32 in transfected cells (Omori et al 1996). Expression of the Golgiretained R142W Cx32 mutation in myelinating Schwann cells of transgenic mice resulted in decreased levels of wild type mouse Cx32 and caused demyelination (Jeng et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations from a number of laboratories suggest that most CMTXassociated mutations lead to a loss of Cx32 function (13). Data suggest this loss of function arises either through defects in trafficking of the mutant protein (14)(15)(16)(17)(18) or through alteration of properties of the junctions it forms (19)(20)(21)(22)(23)(24)(25). Similarly, studies of human Cx31 (hCx31) suggest that mutations in this connexin may also lead to alterations in trafficking or channel function (26)(27)(28), and some mutations increase cell death when expressed in HeLa, NIH 3T3, or NEB1 cells (26,29).…”
mentioning
confidence: 99%